Peran Pendidikan Agama Islam dalam Membentuk Karakter Siswa di Era Digital: Studi Pada SMK Negeri 1 Binjai - Muhammad Rangga Pramana; Oktrigana Wirian (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) in shaping students’ character in the digital era at SMK Negeri 1 Binjai. The research employed a descriptive qualitative method with a phenomenological approach. Data were collected through classroom observations, religious activities, interviews with PAI teachers, and questionnaires distributed to 50 tenth-grade students. The findings reveal that PAI plays a crucial role in instilling key character values, including discipline, honesty, responsibility, religiosity, and digital ethics. PAI teachers utilized interactive media, educational videos, and digital Qur’an applications, which enhanced students’ enthusiasm and facilitated better understanding of the subject matter. Based on the questionnaire results, 83% of students stated that PAI improved their discipline, 77% reported being more cautious in using social media, and 87% acknowledged that PAI fostered a greater sense of responsibility toward themselves and others. However, 60% of students still struggled to control their gadget usage, particularly for entertainment and online games. This indicates the need for continuous guidance and supervision from both teachers and parents. Overall, the study emphasizes that the effectiveness of PAI in the digital era depends on teachers’ competence in integrating technology, the role of exemplary behavior, and strong collaboration between schools and families. Therefore, PAI not only serves as a medium for delivering religious values but also as a vital instrument for shaping Islamic character, enabling students to face moral and social challenges in the digital age.